Peran Organizational Citizenship Behavior sebagai Moderasi Kinerja Pegawai dinilai dari Employee Engagement dan Kepuasan Kerja di Kantor Kecamatan Tarokan Kab. Kediri - Syamsiyah, Muhammad Zaenal Alfanani; Bambang Suwarsono; Brahma Wahyu K. (International Forum of Researchers and Lecturers, 2025)
This study examines the role of organizational citizenship behavior (OCB) as a moderator in the relationship between employee engagement, job satisfaction, and employee performance at the Tarokan District Office in Kediri Regency. The research focuses on analyzing how these variables interact and influence each other within the organizational context. The findings indicate that employee engagement has a significant impact on employee performance. This suggests that when employees are more engaged in their work, they tend to exhibit higher levels of performance. Similarly, job satisfaction also significantly influences employee performance. Employees who are satisfied with their work environment and tasks tend to perform better in their roles. However, the study reveals that organizational citizenship behavior does not significantly influence employee performance. This implies that while OCB is often considered a valuable aspect of employee behavior, it does not directly affect how well employees perform their tasks in this particular setting. Additionally, employee engagement does not significantly affect organizational citizenship behavior, indicating that engaged employees do not necessarily engage in extra-role behaviors like helping others or going beyond job requirements. The research also shows that job satisfaction does not have a significant effect on organizational citizenship behavior, which suggests that employees’ satisfaction with their work does not automatically lead to behaviors that contribute to the broader success of the organization. Furthermore, neither employee engagement nor job satisfaction significantly influences employee performance through organizational citizenship behavior, indicating that OCB does not serve as an effective moderator in these relationships. In conclusion, the main factor in improving employee performance is organizational citizenship behavior does not play a significant moderating role in this dynamic at the Tarokan District Office.